Temporal Analysis of ISCCP Image Sequences. - DaPonte, John (1998)
Keywords: dept.csc; faculty_collection; sabbatical_report

Internet based data collection and analysis - Workman, R.; Beatty, E.; Workman, D. (IOS Press, 1998)
This paper will discuss Internet based data collection and analysis utilizing a Windows 95 and a UNIX hosted system. Forms on the World Wide Web (WWW) that illustrate the use of this technology in medical research, conference registration, and. patient care will be highlighted. Some of the details involved with creating data collection forms will be presented. The paper concludes with the recommendation that the Health Telematics curricula should include a unit on creating Internet based data collection forms.
Keywords: *Computer Communication Networks; *Data Collection/mt [Methods]; Computer Communication Networks; Data Collection; Data Collection/is [Instrumentation]; Data acquisition; Data collection; Health; Humans; Internet based; Medical Informatics; Medical Informatics/og [Organization & Administration]; Medical research; Patient care; Telematics; Wireless telecommunication systems; World wide webs (WWW); article; computer network; dept.csc; human; information processing; instrumentation; medical informatics; methodology; organization and management; ⛔ No DOI found

College to work transitions: students draw their futures - Lancor, Lisa; Karanian, B A (1998)
This preliminary investigation considers undergraduate student perceptions with respect to their professional future. `No one warned me it would be like this,' and `These are the things that college never taught me,' are typical comments that are heard from the young workforce. This paper addresses future plans and predictions of students from two New England institutions of higher learning by utilizing a variety of strategies. Methods to elicit data include in-class activities and carefully designed questionnaires. These exercises have been designed to uncover images and themes concerning transition from college to the workplace. Issues include technical and communication skills, leadership roles, corporate politics, group dynamics, and gender diversity in the workplace.
Keywords: Employment; Engineering education; Professional aspects; Student perceptions; Students; dept.csc

Application of evolutionary techniques to temporal classification of cloud systems using satellite imagery - Parikh, Jo Ann; Daponte, John S; Vitale, Joseph N; Tselioudis, George (SPIE, 1998)
The objective of this research is to automate the classification of the temporal behavior of storm cloud systems based on measurements derived from consecutive satellite images. The motivation behind this study is to develop improved descriptions of cloud dynamics which can be used in general circulation models for prediction of global climate change. Analysis was applied to the International Satellite Cloud Climatology Project (ISCCP) low resolution cloud top pressure database for the first six days in April, 1989. A total of 296 midlatitude storm cloud components were tracked between consecutive 3-hour time frames. For each pair of components, temporal correspondence events were classified as either 1.) direct, 2.) merge, 3.) split, or 4.) reject. The reject class, which was used primarily to categorize pairs of unrelated systems, included storm cloud system dissipation and creation as well. Statistical, neural network, and evolutionary techniques were developed for finding solutions to the storm cloud correspondence problem. Evolutionary techniques applied to the problem consisted of 1.) a constraint-handling hybrid evolutionary technique and 2.) a genetic local search algorithm. The results demonstrate the potential of evolutionary techniques to yield meteorologically-feasible solutions, given appropriate constraints, to the two-frame storm tracking problem. © 1998 SPIE. All rights reserved.
Keywords: Artificial intelligence; Climate change; Climate models; Cloud tracking; Correspondence problem; Correspondence problems; Evolutionary techniques; General circulation model; Genetic algorithms; Genetic local search algorithm; Global climate changes; Image classification; International satellite cloud climatology projects; Neural networks; Satellite imagery; Storms; Temporal classification; dept.csc

Developing integrated Web and database applications using JAVA applets and JDBC drivers - Yang, Andrew; Linn, James; Quadrato, David (ACM, 1998)
In this paper we have discussed different types of JDBC drivers under the context of a two-tier client/server model. However, it is entirely possible to use them to develop a multi-tier client/server application. The integration of web servers with database servers via the use of JAVA applets and JDBC drivers is useful for the teaching of database programming and web-based application development. The applet that we have developed, along with our experience of configuring the JDBC and JAVA environment, was used in a database course. Students built more complicated database/web applications on top of this sample applet. Future extension of our work may involve the following items: • the security implication of using JDBC drivers in a multiple, heterogeneous DBMS environment • the possible interaction of JDBC with firewalls and proxy servers • the evaluation of JDBC drivers under the context of real-world applications, especially their reliability and performance.
Keywords: Computer science; Database systems; High level languages; Java database connectivity (JDBC) drivers; Java programming language; Object oriented programming; Wide area networks; dept.csc